MENINGKATKAN HASIL BELAJAR BAHASA INDONESIA DENGAN MENGGUNAKAN METODE PEMBELAJARAN PROBLEM SOLVING DI SDN 010 TALONTAM KECAMATAN BENAI - Hasniwati Hasniwati (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2019)
This research aims to improve Indonesian language learning outcomes by using a problem solving learning model of class VI SDN 010 Talontam. Class action research is an effort to improve various kinds of learning problems in the classroom. Data analysis of teacher activities after the study is in the initial data of 52%, then the second meeting is 64%, the third meeting is 75%, and at the fourth meeting is 90%. Student activity data after research has increased at the first meeting only by 55%, at the second meeting at 67, at the third meeting at 73%, and at the IV meeting at 92%. Improved learning outcomes are obtained after a daily test, in UH I the average student learning outcomes are 75 and in UH II 89 is a significant increase. By looking at the data above that the application of an effective problem solving learning model to improve Indonesian learning outcomes in class VI SDN 010 Talontam District of Benai.